Biosimilars in rheumatic diseases: structural and functional variability that may impact clinical and regulatory decisions. Issue 12 (December 2016) - Lakhanpal, Amit; Brahn, Ernest
Abstract Biologics as therapeutic interventions for human disease represent both a distinctly modern novelty and an echo of ancient, or at least old, medical practice. The similarity lies in the sense that in both the synthetic effort occurs in living organisms (an extract of a plant, animal tissue, or a cell culture) while the difference is apparent in the bioengineering required in modern methods and the corresponding flexibility to customize the therapeutic product. Although the concept of looking to living systems as a source of medically useful compounds either for research or for actual patient care has never vanished, the development of biochemistry and advances in medicinal chemistry made production by total synthesis the standard for a safe, reliable, and commercial drug production at sufficient scale. In this interval was where much of the modern apparatus for approving medical therapies came to be developed, and as such, the most proper extension of the regulatory regime to modern biologics is not entirely obvious. In particular, the notion of generics for off-patent conventional pharmaceuticals and their role in the marketplace with respect to increasing the accessibility of treatment is not congruent with the relationship between what are known as biosimilars and off-patent originating biologics. In this article, we review elements of the scientific basis for challenges in the production, use, and regulation of biosimilars. In light of these advances, we propose suggestions to modify constraints on biosimilar regulations in the interest of patient care and access to therapies.